Recommendations for intrauterine contraception: a randomized trial of the effects of patients' race/ethnicity and socioeconomic status - Dehlendorf, Christine; Ruskin, Rachel; Grumbach, Kevin; Vittinghoff, Eric; Bibbins-Domingo, Kirsten; Schillinger, Dean; Steinauer, Jody (American journal of obstetrics and gynecology, 2010)
Recommendations by health care providers have been found to vary by patient race/ethnicity and socioeconomic status and may contribute to health disparities. This study investigated the effect of these factors on recommendations for contraception. One of 18 videos depicting patients of varying sociodemographic characteristics was shown to each of 524 health care providers. Providers indicated whether they would recommend levonorgestrel intrauterine contraception to the patient shown in the video. Low socioeconomic status whites were less likely to have intrauterine contraception recommended than high socioeconomic status whites (odds ratio [OR], 0.20; 95% confidence interval [CI], 0.06–0.69); whereas, socioeconomic status had no significant effect among Latinas and blacks. By race/ethnicity, low socioeconomic status Latinas and blacks were more likely to have intrauterine contraception recommended than low socioeconomic status whites (OR, 3.4; and 95% CI, 1.1–10.2 and OR, 3.1; 95% CI, 1.0–9.6, respectively), with no effect of race/ethnicity for high socioeconomic status patients. Providers may have biases about intrauterine contraception or make assumptions about its use based on patient race/ethnicity and socioeconomic status.